Coffee: Lighting Its Complex Ground Truth and Percolating Its Molecular Brew - Róża Paterek; Sive Geoghegan; Bernadette S. Creaven; Aoife Power (Beverages)
Coffee is one of the most widely traded commodities worldwide and its popularity is only increasing. The International Coffee Organisation (ICO) reported a 6% increase in global production in 2020 to 10.5 million tonnes. Coffee production is quite involved (from sowing to harvesting, processing, packaging, and storage); consequently, the industry faces major challenges in terms of the assessment of its quality, flavour, and the components which contribute to coffee’s characterisation, as well as the sustainability of coffee production and global trade. This has prompted multiple studies on the nature of the aroma and taste of the many varieties of coffee around the world, which has resulted in the identification of approximately 1000 volatile compounds and the development and implementation of upwards of 100 lexicons to describe the specific sensory characteristics of coffee. The complex nature of coffee has necessitated the development and incorporation of new analytical methodologies, such as multidimensional separation technologies and spectroscopy coupled with multivariant analysis, to qualify the essential characteristics of coffee’s flavour. This work aims to review the research on coffee’s flavour, covering the roasting process of coffee beans, the volatile and non-volatile components generated by this process, and the chemical reactions responsible for their formation, as well as coffee’s sustainability, the coffee value chain, and various forms of regulation, particularly the current emphasis on ‘fair trade’.